Uso e conservação de Piper cernuum Vell. (Piperaceae) na Mata Atlântica: I. Fenologia reprodutiva e dispersão de sementes - Mariot, A. (2003)
The pariparoba (Piper cernuum Vell.), a native plant from the Atlantic Tropical Forest (ATF), has been commonly used in folk medicine. Works seeking the exploitation of P. cernuum natural populations need to be accomplished, seeking compatibility in obtaining income rates and preservation of ATF. The present work aimed to study the reproductive phenology and seed dispersal in P. cernuum natural population in the counties of Sete Barras/SP (Parque Estadual Intervales - PEI). The population of P. cernuum studied in PEI presented continuously bud-inflorescences, green-infrutescences and bud-inflorescence emission, with variation among individuals. Fruit-set average was of 9.1%, varying among individuals. Shading and foliar damage presented negative effect on the fruit-set. Three species of bats were identified as potential dispersors of the P. cernuum seeds: Carollia perspicillata, Anoura geoffroyi and Artibeus sp. The foragement strategy observed was the withdrawal of some seeds per infrutescence per flight. This strategy increases the potential in establishing new plants as well as in increase the potential of gene flow in comparison with the entire infrutescence plant eaten at the night perches. In consequence, the results of reproductive phenology and seed dispersal ecology presented in this work can help to establish management and conservation strategies of P. cernuum natural populations in the ATF.